Coeliac disease in the COVID-19 pandemic: does HLA have a protective effect?. (31st December 2022) - Greco, N.; Meacci, A.; Mora, B.; Vestri, A.; Picarelli, A.
Abstract: Background: The coronavirus disease 2019 (COVID-19), an acute respiratory disease caused by a novel coronavirus (SARS-CoV-2), is emerging as a worldwide public health emergency. Several scientific contributions reported the potential relevance of human leukocyte antigen (HLA) polymorphism and susceptibility to viruses, such as SARS-CoV. In our study, we examined a population of coeliac subjects presenting the HLA haplotype DQ2 and/or DQ8. Our aim was to evaluate whether HLA DQ2 and/or DQ8 haplotype play a role in SARS-CoV-2-infection. The aim was also to evaluate the difficulty in following the gluten-free diet due to all the adversities produced by the pandemic, such as the food supply disruption, and the difficulties in managing the clinical follow-up. Methods: 191 consecutive coeliac patients completed a questionnaire on their current clinical status, psychological effects, and management of the gluten-free diet experienced during the COVID-19 pandemic and questions regarding possible SARS-CoV-2 infection. Results: Out of the 191 patients who participated in the study, 42 were full-blown coeliac and 149 were in remission. From the answers provided, 84.8% of patients declared that they no longer consider themselves vulnerable to COVID-19 as they suffer from coeliac disease; 94.2% of patients did not encounter any difficulties in managing the gluten-free diet or in acquiring specific foods and 64.9% of patients in our study underwent diagnostic testing for SARS-CoV-2. Out of this number, 31.5% did so due to contacts with subjects affected by COVID-19, 26.6% for work related reasons, 11.3% due to flu-like symptoms and 30.6% for other reasons. Only 5.8% of the enrolled patients received a diagnosis of COVID-19. Out of all the patients in our population who were diagnosed with COVID-19, 94.8% developed no symptoms and none of them needed hospitalization or intensive care. Conclusion: The hypothesis that the HLADQ2 and/or DQ8 haplotype plays a protective role against SARS-CoV-2 infection, as against other viral infections, is intriguingly suggestive. KEY MESSAGES: COVID-19 as a public health emergency; SARS-CoV-2 and possible complications in coeliac disease; Role of HLA DQ2 and/or DQ8 in SARS-CoV-2 infection.